Un Atlántico : algunas historias de resiliencia - Eversley Torres, Francisco Javier (Corporación Universitaria Americana, 2023)
When reading "Un Atlántico: some stories of resilience", it is impossible not to feel the heart ache at the thought of the pain still felt by its protagonists; but, at the same time, the feeling of admiration is immense. They are people who, despite the circumstances, have an unthinkable capacity to overcome adversity and rise from the ashes. For this reason, he began by highlighting the title of the book. There is nothing better than using the word resilience to pay tribute to the victims of the horror of war, of discrimination, of society itself, of our country; with whom, without knowing it, we cross paths all the time. We are a country whose people have an unparalleled capacity to overcome negative events that would sink anyone. And, although it sounds like a cliché phrase, the country of Macondo is also the country of resilience. It is enough to read the stories narrated in this book.